1981
DOI: 10.1084/jem.153.4.766
|View full text |Cite
|
Sign up to set email alerts
|

Tumor cell anti-oxidant defenses. Inhibition of the glutathione redox cycle enhances macrophage-mediated cytolysis

Abstract: The basis of resistance to oxidative injury was studied in six murine tumor cell lines that differed 54-fold in their resistance to enzymatically generated H(2)0(2). The tumors varied 56.7-fold in their specific activity of catalase, 5.3-fold in glutathione peroxidase (GPO), 3.3-fold in glutathione reductase (GR), and 2.7-fold in glutathione. There was no correlation among the levels of the three enzymes, and tumor cell resistance to lysis by H(2)0(2). However, the logarithm of the flux of H(2)0(2) necessary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(75 citation statements)
references
References 39 publications
2
73
0
Order By: Relevance
“…To determine which extracellularly generated oxygen reduction products rapidly lyse human cells, and therefore which enzymes might be involved in defense against oxidative cytolysis, we compared the susceptibility of fibroblasts, SK-BR-1-III, SK-BR-2-III, erythrocytes, and CAMA-I to H202,°-, and OH. Lysis first was attempted with the H202 generating system of glucose oxidase and glucose, which lysed most murine tumors tested (1). However, fluxes of H202 (nanomoles per minute per 0.2 ml) up to 3 for fibroblasts, 14 for SK-BR-l-III, 15 for SK-BR-2-Ill, 21 for erythrocytes, and 105 for CAMA-I failed to produce substantial lysis (not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine which extracellularly generated oxygen reduction products rapidly lyse human cells, and therefore which enzymes might be involved in defense against oxidative cytolysis, we compared the susceptibility of fibroblasts, SK-BR-1-III, SK-BR-2-III, erythrocytes, and CAMA-I to H202,°-, and OH. Lysis first was attempted with the H202 generating system of glucose oxidase and glucose, which lysed most murine tumors tested (1). However, fluxes of H202 (nanomoles per minute per 0.2 ml) up to 3 for fibroblasts, 14 for SK-BR-l-III, 15 for SK-BR-2-Ill, 21 for erythrocytes, and 105 for CAMA-I failed to produce substantial lysis (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Weiss et al (48) showed that huma umbilical vein endothelial cells were sensitive to lysis by H2C released from stimulated neutrophils. The concentration c H202 generated by the neutrophils was 67 ,M, 1 (26). Even in our study, where human fibroblasts were insensitive to fluxes of H202 attainable with glucose oxidase or xanthine oxidase, the cells were rendered up to 20-fold more sensitive to H202 by inhibition of the GSH redox cycle with BSO or BCNU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glutathione (GSH) is a tripeptide of cysteine, glutamic acid and glycine (L-γ-glutamyl-L-cysteinyl-glycine) and is a ubiquitous major antioxidant in vivo [14,21,26]. The antioxidative activity of GSH is exhibited by supplementing and removing reactive oxygen species generated in the living body, and many recent findings have indicated its importance in the immune system [8,13,26].…”
mentioning
confidence: 99%
“…Previous murine investigations have demonstrated that glutathione depletion increases tumor cell susceptibility to macrophage-mediated oxidative injury. 36 As CD68 is a known prognostic marker in lymphoma and can be evaluated using immunohistochemistry, future investigations of imexon should investigate CD68 expression further.…”
Section: Discussionmentioning
confidence: 99%